The Positive Effects of Cancer Survivor Support Service on Distress in South Korea: A Nationwide Prospective Study - Lee, Hyun Jeong; Kim, Young Ae; Ryu, Seong Yeob; Chun, Mison; Yim, Chang-Yeol; Kang, Hee-Taik; Kang, Jung Hun; Huh, Jung-Sik; Kim, Jong-Heun; Lim, Kyu-Hyoung; Jung, So-Youn; Kwon, Hyoung-Cheol; et al. (Frontiers in Medicine, 2022)
Background & Aim: Cancer survivors are gradually increasing, however, they suffer from various difficulties. We aimed to investigate the characteristics of cancer survivors and the effects of the services of the Korean Cancer Survivorship Center Pilot Project launched by the South Korean government on distress. Methods: A prospective observational cohort study was performed on cancer survivors who completed primary treatment. Cancer survivors’ distress and symptoms such as fatigue, pain, depressive mood, anxiety, and insomnia were evaluated by well-trained nurses. Regarding their needs, medical and psychosocial support services were provided. Results: This study included 1,921 cancer survivors, with a mean age of 57.3 years (68.7% females). Breast cancer was most common, followed by stomach and colorectal cancer. Psychosocial and medical support decreased the percentage of the high-distress group from 50.9% to 30.5% and decreased the percentage of cancer survivors with high scores in fatigue, pain, anxiety, depressive mood, and insomnia. The independent predictors of a low distress level after the use of the services were older age, the relief of fatigue, pain, and insomnia. Conclusion: This study showed that psychosocial and medical support is associated with the lower distress and physical and mental symptoms of cancer survivors. Psychosocial and medical support could contribute to distress relief in cancer survivors. Further management strategies for fatigue, pain and insomnia are required.